An open, observational, three-arm clinical study of 2–3 cycles of treatment as neoadjuvant therapy in operable locally advanced non-small cell lung cancer: An interim analysis - Gu, Linping; Wang, Xue; Sun, Yile; Xu, Yunhua; Niu, Xiaomin; Zhao, Ruiying; Yao, Yaxian; Jian, Hong; Han, Yuchen; Wei, Jinwang; Chen, Zhiwei; Lu, Shun (Frontiers in Immunology, 2022)
Background: An open, observational, three-arm clinical study aimed at investigating the efficacy of different neoadjuvant therapy (neoadjuvant immunotherapy with(out) chemotherapy, neoadjuvant chemotherapy, and neoadjuvant targeted therapy) in operable locally advanced non-small cell lung cancer (NSCLC) has been conducted (NCT04197076). We report the first clinical results of the planned interim analysis after 53 patients were enrolled. Methods: This study was conducted in Shanghai Chest Hospital, and included eligible NSCLC patients who were 18 years old and had clinical stage IA-IIIB. 49 patients were scheduled to receive surgery successfully within 4-6 weeks after 2 cycles of neoadjuvant treatment consisting of immunotherapy (24 patients), chemotherapy (16 patients), and targeted therapy (9 patients) regimen on the day of each 21-day cycle. The primary endpoint was the major pathological response (MPR), and then the tumor regression rate (TRR). Results: The TRR of neoadjuvant immunotherapy arm, neoadjuvant targeted therapy arm, and neoadjuvant chemotherapy arm after 2 cycles were 25.10±23.73, 22.97±18.99, and 18.42±23.78 respectively, but there was no significant difference among the three arms (P=0.59). Different neoadjuvant therapy had statistical significance on postoperative pathological tumor downstaging (P=0.017). More importantly, we found that the curative effect of neoadjuvant immunotherapy arm in MPR was better than that of neoadjuvant chemotherapy arm and neoadjuvant targeted therapy arm (45.8% vs. 18.8% vs. 0.0%) (P=0.006; 95%CI, 0.008-0.012). In addition, the pathologic complete response in neoadjuvant immunotherapy arm was better than that of neoadjuvant chemotherapy arm and neoadjuvant targeted therapy arm (5/24 vs. 1/16 vs. 0/9). Conclusions: Our interim data analysis indicates that neoadjuvant immunotherapy is more promising in TRR and MPR than neoadjuvant chemotherapy and neoadjuvant targeted therapy for operable locally advanced NSCLC patients while its long-term effect needs to be further studied. Trial registration: ClinicalTrials.gov, NCT04197076.